2018
DOI: 10.1182/blood-2018-99-113939
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Mapping of Sickle Cell Disease in Northwest Tanzania: The Tanzania Sickle Surveillance Study (TS3)

Abstract: Tanzania ranks third in Africa for the estimated number of annual births with sickle cell disease, but these estimates are based on sparse data from small studies reported over the past 50 years. A recently completed surveillance study from Uganda documented substantial variation in the prevalence of sickle cell trait and disease across the country. Tanzania lacks a national newborn screening program, and no contemporary multi-regional screening of infants has been undertaken. We designed and conducted a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We have brought together strong accounts and recommendations from the interviews and discussions done with families on what are the key issues to consider when communicating SCT results. Families understanding of the results is of priority especially in places where the burden of the SCD is high (Ambrose, Makani, et al, 2018; Fanning, 2016; Ndeezi et al, 2016). Results from this study has shown that families understanding of the results provided is still challenging.…”
Section: Discussionmentioning
confidence: 99%
“…We have brought together strong accounts and recommendations from the interviews and discussions done with families on what are the key issues to consider when communicating SCT results. Families understanding of the results is of priority especially in places where the burden of the SCD is high (Ambrose, Makani, et al, 2018; Fanning, 2016; Ndeezi et al, 2016). Results from this study has shown that families understanding of the results provided is still challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Bugando Medical Centre (BMC) located in the Mwanza region serves as the zonal referral hospital for the lake and western zone of Tanzania, where the annual births of children with SCD are estimated to be one of the highest in the world [ 24 ]. A pilot NBS for SCD program implemented at BMC between August and September 2014 reported 1.4% of children with SCD out of 919 children screened and 19.7% children with traits [ 25 ]. Inclusion of BMC was motivated by both the prevalence of SCD in the region served by the hospital as well as their experience in implementing NBS for SCD [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…A pilot NBS for SCD program implemented at BMC between August and September 2014 reported 1.4% of children with SCD out of 919 children screened and 19.7% children with traits [ 25 ]. Inclusion of BMC was motivated by both the prevalence of SCD in the region served by the hospital as well as their experience in implementing NBS for SCD [ 24 , 25 ]. Both sites have at least one day each week dedicated clinic for sickle cell patients.…”
Section: Methodsmentioning
confidence: 99%
“…Bugando Medical Centre (BMC) located in Mwanza region is serving as the zonal referral hospital for the lake and western zone of Tanzania where, the annual births of children with SCD is estimated to be one of the highest in the world [26]. A pilot NBS for SCD program implemented at BMC between August to September 2014, reported 1.4% of children with SCD out of 919 children screened and 19.7% children with trait [27]. Inclusion of BMC was motivated by both prevalence of SCD in the region served by the hospital as well as their experiences in implementing NBS for SCD [26, 27].…”
Section: Methodsmentioning
confidence: 99%
“…A pilot NBS for SCD program implemented at BMC between August to September 2014, reported 1.4% of children with SCD out of 919 children screened and 19.7% children with trait [27]. Inclusion of BMC was motivated by both prevalence of SCD in the region served by the hospital as well as their experiences in implementing NBS for SCD [26, 27]. Figure 1 (A) and (B) below are maps of Dar es Salaam and lake zone regions showing geographical locations of health facilities included in this study.…”
Section: Methodsmentioning
confidence: 99%